Acute traumatic stress among surgeons after major surgical complications. - Pinto, A; Faiz, O; Bicknell, C; Vincent, C (Elsevier, 2014)
BACKGROUND: Patient harm resulting from medical treatment may be a traumatic experience for health care staff. This study examined surgeons' levels of traumatic stress in the aftermath of the most recent major complication that happened in their patients' care and its relationship with surgeons' coping strategies, causal attributions, and perceived institutional culture around surgical complications. METHODS: Forty-seven general and vascular surgeons from 3 National Health Service Trusts in London, UK completed a questionnaire assessing the aforementioned variables (64.4% response rate). RESULTS: One-third of the participants reported traumatic stress of clinical concern 1 month after the incident. The use of self-distraction (P < .05) and being a general surgeon (P < .05) were predictive of traumatic stress of clinical concern in multiple logistic regression analysis. CONCLUSIONS: Some surgeons may experience acute traumatic stress after serious surgical complications. The extent to which this is of clinical concern is associated with their use of self-distraction as well as the clinical setting. Health care organizations need to attend to surgeons' psychological needs in the aftermath of serious adverse events.